Analysis and Study of the Choice of the Superelevation Angle Value - Harutyunyan, Valerik; Mosikyan, Karapet; Hayrapetyan, Anna; Harutyunyan, Anahit (Scientific Papers of National University of Architecture and Construction of Armenia, 2024)
During the curvilinear motion in the turns of the highways, the car is affected by centrifugal forces, which tend to pull the car out of the turning trajectory, causing an emergency situation. The present article touches upon the forces affecting the car during curvilinear motion, especially in the conditions of the longitudinal slope of the road, the methodology of their calculation and the characteristics of the superelevation, etc. The change of the attachment coefficient, the magnitude of the lateral forces were analyzed, and based on this, the analytical expression for the calculation of the magnitude of superelevation angle, depending on the radius of curvature and the speed during the turn was derived. The existing methodology for determining the angle of turn in road construction and design is also presented and a comparative assessment is made.